THE RELATIONSHIP BETWEEN MANAGEMENT CONTROL SYSTEMS AND FINANCIAL PERFORMANCE IN MANUFACTURING COMPANIES - Siti Intan Nurdiana Wong Abdullah; Puspa Rini; Nirsetyo Wahdi; Sylvia Kartika Dhamayanti (CV. Fahr Publishing, 2025)
This study aims to investigate the relationship between Management Control Systems (MCS) and financial performance in manufacturing companies operating in emerging economies, with a specific focus on Indonesia. It further explores the moderating effects of digital maturity and organizational culture to understand how contextual factors influence the effectiveness of MCS. Using a quantitative approach, data were collected through structured questionnaires from 120 financial and operational managers across Indonesian manufacturing firms. The research employed multiple linear regression and moderated regression analysis (MRA), supported by SmartPLS and SPSS software, to test the direct and interaction effects between variables. The results reveal that both diagnostic and interactive control systems significantly impact financial performance, with interactive controls demonstrating a stronger influence. Moreover, digital maturity positively moderates the relationship between MCS and financial outcomes, while organizational culture shows no significant moderating effect. The novelty of this research lies in its integration of digital readiness as a strategic enabler within the MCS framework, offering new theoretical and empirical insights, especially in the context of small and medium-sized enterprises (SMEs) in developing markets. This study also contributes methodologically by applying a dual-theory approach—combining contingency theory with dynamic capabilities theory—to better capture the adaptive use of control systems under technological disruption. In conclusion, effective MCS implementation, especially when supported by digital infrastructure, can enhance financial performance and strategic agility, making it a critical tool for organizational competitiveness in globalized markets.